Poster No. 132 HTAD PATIENT PATHWAY: Strategy for diagnostic work-up of patients and families with (suspected) Heritable Thoracic Aortic Diseases (HTAD). A statement from the HTAD Working Group of VASCERN. (21st October 2022) - de Backer, Julie; Caruana, Maryanne; Baars, Marieke; Bashiardes, Evi; Benke, Kalman; Bjorck, Erik; Codreanu, Andrei; de Moya Rubio, Elena; Dumfarth, Julia; Evangelista, Arturo; Groenink, Maarten; Kallenbach, Klaus; et al.
Abstract: Background: Timely diagnosis of patients with Heritable Thoracic Aortic Diseases (HTAD) is essential to avoid (often fatal) aortic dissection. Experts of the HTAD rare disease working group of the European Reference Network of Rare Vascular diseases (vascern) aimed to propose a pathway to: (1) improve patient care by diminishing time to diagnosis; (2) facilitate the establishment of a correct diagnosis, using molecular genetics when possible, which may lead to a more personalized treatment; (3) exclude the diagnosis in unaffected persons (family screening); (4) avoid overuse of financial and personnel resources. Material and methods: This pathway is a consensus at expert level. It was generated based on available guidelines when possible. Discussion items were listed and, where necessary, items were included in a questionnaire sent out for voting and discussion over monthly teleconference calls. Results and conclusions: Pathway Elements include Thoracic aortic aneurysm – and dissection, Bicuspid Aortic Valve, Medium-sized artery aneurysms/dissection, Extravascular features and Family History. Recommendations for the evaluation of patients and family members are provided. This pathway is advised to implement standardisation of diagnostic workup and follow-up of patients with suspected HTAD and the screening of their relatives and it focuses on patients with heritable aortic diseases whether syndromic or not. It is subject to adjustment with better recognition of new entities, and with the technical progress and increased availability of genetic testing.